2021
DOI: 10.1145/3478513.3480530
|View full text |Cite
|
Sign up to set email alerts
|

Physical light-matter interaction in hermite-gauss space

Abstract: Our purpose in this paper is two-fold: introduce a computationally-tractable decomposition of the coherence properties of light; and, present a general-purpose light-matter interaction framework for partially-coherent light. In a recent publication, Steinberg and Yan [2021] introduced a framework that generalises the classical radiometry-based light transport to physical optics. This facilitates a qualitative increase in the scope of optical phenomena that can be rendered, however with the additional expressib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…It is often important to evaluate the AHG functions at 0, e.g., for computation of the peak energy of optical beams or the determination of the total energy carried by a wave ensemble [13]. The next corollary provides an explicit expression for the values at 0 and may admit interesting combinatorics.…”
Section: Corollary 38 (Dimensional Decomposition) With Smentioning
confidence: 99%
See 1 more Smart Citation
“…It is often important to evaluate the AHG functions at 0, e.g., for computation of the peak energy of optical beams or the determination of the total energy carried by a wave ensemble [13]. The next corollary provides an explicit expression for the values at 0 and may admit interesting combinatorics.…”
Section: Corollary 38 (Dimensional Decomposition) With Smentioning
confidence: 99%
“…The positive definite matrix can be used for the representation of spatial deformations, geometric properties and energy tensors of structured optical beams, and potential other future applications. In the context of optical coherence theory, it was shown that this anisotropy matrix has a clear physical meaning [13]: the spatial coherence of light. This allows for the representation of a large family of coherence functions using a limited count of AHG modes, making the representation computationally-tractable.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to PLT, Cuypers et al [2012]; Oh et al [2010] also aim to simulate the global evolution of light's optical coherence, by using a form of a "generalized radiance" (the Wigner distribution function in its optical context [Testorf et al 2010]), acting as a descriptor of partially-coherent light. Further comparison between this line of work and PLT is given by Steinberg and Yan [2021b]. We stress that the sampling problem inevitably arises in these approaches, as they quantify and propagate partiallycoherent light.…”
Section: Related Workmentioning
confidence: 99%